Security flaws and improvement to a wireless authentication protocol with anonymity - PENG Hua-xi; FENG Deng-guo (Tongxin xuebao)
The anonymous security flaw of an authentication protocol with anonymity for wireless networks which was proposed by Zhu, et al. was analyzed, and an improved protocol to a wireless authentication protocol with anonymity （IWAA） was proposed. The anonymous security of the improved protocol was analyzed in a formal way. The research results reveal that the improvement can not only achieve authentication but also have a good anonymous property and achieve the ideal security requirements of anonymity for wireless network.